Burkitt-Like Lymphoma with 11q Aberration: A Case Report and Review of a Rare Entity - Sepideh N. Asadbeigi; Chelsey D. Deel (Case Reports in Hematology)
Burkitt-like lymphoma with 11q aberration is a rare diagnostic entity commonly occurring in children and young adults with a nodal presentation. This entity shares many similar morphologic and immunophenotypic features with conventional Burkitt lymphoma and other aggressive B-cell lymphomas, making its recognition challenging. However, the presence of its characteristic 11q gain/loss pattern is helpful in the diagnosis. We report a case of Burkitt-like lymphoma presenting as a right neck mass in a 17-year-old female patient that demonstrated no improvement with antibiotic therapy. The neoplasm displayed a diffuse proliferation of intermediate-sized atypical lymphoid cells with prominent nucleoli in a background of apoptotic debris, morphologically raising concern for conventional Burkitt lymphoma. Subsequent immunohistochemical and cytogenetic studies established the most likely diagnosis of Burkitt-like lymphoma with 11q aberration. Though rare, Burkitt-like lymphoma exhibits significant morphologic overlap with other high-grade B-cell lymphomas, making it an important entity to consider on the differential diagnosis of these lesions.